(untitled) (International Journal of Engineering and Computer Science, 2014)
Fingerprint matching is one of the most efficient and successful technique for human identification with easy to implement and get accurate results. This paper presents a review on study and implementation of a fingerprint recognition system based on Minutiae based matching quite frequently used in various fingerprint algorithms and techniques. This approach mainly involves extraction of unique identification points called minutiae points from the captured fingerprint images and then performing fingerprint matching based on the number of minutiae pairings among two fingerprints in question. The spurious minutia are removed by identifying the false percept minutia at the extraction stage.